(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internet of Things (IoT) prevails in the technological world among various technologies. The creation of IoT brings about a renaissance in the smart connected world. The security issues in IoT have risen alarmingly in recent years. These security issues are inalienable in IoT network. Particularly, attacks in IoT network layer exploit the entire IoT system. The most common attack which makes a big impacts on RPL based IoT network is rank attack. The impacts of rank attack could be reduced by providing efficient technique to identify and mitigate the rank attack. In this paper, a technique “LEACE” is proposed to identify and mitigate rank attack based on the level of the nodes in the network. Rank and level of the nodes are corresponded in the IoT system. For identifying rank attack, the level and rank of the nodes are checked whether the nodes’ rank are corresponded with their level. The proposed technique outperforms the VeRa technique. It provides better results than the VeRa in terms of packet delivery ratio, detection accuracy and throughput.